2009
DOI: 10.1254/jphs.08299fp
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phenotypic and Functional Maturation of Dendritic Cells by Manassantin A

Abstract: Abstract. Manassantin A (MSA) inhibits nitric oxide production by macrophages through the inhibition of NF-κB activation, but the effect of MSA on dendritic cells has not been elucidated yet. Here we investigated the inhibitory effects of MSA on immune functions of dendritic cells (DCs). MSA inhibited lipopolysaccharide (LPS)-induced phenotypic maturation of DCs, which was proved by the decreased expression of CD40, CD80, CD86, MHC-I, and MHC-II. MSA also inhibited functional maturation of DCs, that is, decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This finding is consistent with the previous observation that manassantin A attenuates the lipopolysaccharide (LPS)-induced expressions of TNF-α, IL-6, and IL-1β in dendritic cells (DCs) and inhibits the activations of nuclear factor kappa B (NF-κB), extracellular signal-regulated kinases (ERKs), p38, and c-Jun N-terminal kinases (JNK). 35) Moreover, previous studies have shown that administration of manassantin A inhibits the TNF-α-induced expression of cell adhesion molecules by human umbilical vein endothelial cells 17) and the IL-6-induced activation of signal transducer and activator of transcription 3 (STAT3) in Hep3B cells. 36) Gastric mucus, which is the first line of defense against acid, adheres with epithelium-secreted bicarbonate to serve as a barrier against self-digestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the previous observation that manassantin A attenuates the lipopolysaccharide (LPS)-induced expressions of TNF-α, IL-6, and IL-1β in dendritic cells (DCs) and inhibits the activations of nuclear factor kappa B (NF-κB), extracellular signal-regulated kinases (ERKs), p38, and c-Jun N-terminal kinases (JNK). 35) Moreover, previous studies have shown that administration of manassantin A inhibits the TNF-α-induced expression of cell adhesion molecules by human umbilical vein endothelial cells 17) and the IL-6-induced activation of signal transducer and activator of transcription 3 (STAT3) in Hep3B cells. 36) Gastric mucus, which is the first line of defense against acid, adheres with epithelium-secreted bicarbonate to serve as a barrier against self-digestion.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies showing that manassantin A is potent inhibitors of NF-κB activation by the suppression of transcriptional activity of RelA/p65 subunit of NF-κB 20) and manassantin A inhibits nitric oxide production by macrophages through the inhibition of NF-κB activation. 35) Therefore, it suggests that manassantin A has anti-oxidant and anti-inflammatory effects on ethanol-induced gastric lesions by regulation of NF-κB/ iNOS or NF-κB/TNF-α pathway, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the expression of immune stimulatory molecules, such as CD80, CD83, or CD86, and an increase in the production of IL-12, is considered to constitute evidence of DC maturation in the human (20,26), mouse (27), and dog (28). In the present study, we found that DCs induced from dog monocytes increased the expression of the immune stimulatory molecules and IL-12 by IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…Double-stained BMDCs were analyzed by FCM. In addition, parallel experiments were performed at 4°C to determine the nonspecific binding of FITC-dextran to BMDCs [15].…”
Section: The Phagocytosis Of Bmdcs Determined By Fcmmentioning
confidence: 99%